Islamic Home Financing Research: A Bibliometric Mapping and Future Research Directions - Intan Dita Angelina; Wahyudi, Rofiul; Akhmad Arif Rifan; Sunu Prasetya Adi (IJISH (International Journal of Islamic Studies and Humanities), 2025)
The increasing demand for housing financing based on Islamic principles has positioned Islamic Home Financing (IHF) as one of the fastest-growing products within the Islamic banking industry. This phenomenon has triggered a range of academic studies exploring aspects such as financing contracts, consumer behaviour, affordability, and regulatory frameworks. However, these studies remain fragmented, lacking a comprehensive overview of the knowledge structure and research trajectory within the field. This study aims to map the scholarly landscape of IHF through a bibliometric analysis focusing on three main dimensions: co-authorship, co-occurrence, and co-citation. Based on 54 Scopus-indexed documents published between 2000 and 2025, the data were analyzed using VOSviewer. The findings indicate that collaboration networks are dominated by Hanudin Amin from Malaysian institutions, with emerging cross-country and cross-disciplinary partnerships that include sustainability issues. Keyword analysis highlights "Islamic home financing" as a central term, closely associated with the integration of social and commercial finance, consumer behaviour theory (TPB), and environmental concerns. Co-citation analysis reveals a heavy reliance on conventional literature, with classical theories such as TRA and TPB serving as foundational references. The limited research on risk-related issues suggests a significant research gap. This study contributes to the development of a more integrative theoretical foundation for academics and provides practical insights for Islamic banks in designing competitive, sustainable, and globally responsive IHF products.